El impacto ambiental social de los costes de producción de las empresas (2015)
The article is a reflection on the power and control of capitalist enterprises with regards to nature and how, through market expansion, nature as a common good for humanity is exploited in devastating ways, reducing natural resources simple to the buying and selling of goods. Additionally, these goods and services are never including the cost to cover the burden of environmental and social impacts that contribute to destroy the planet. Companies, in complicity with the state governments and international organizations, do not favor the creation of instruments, policies and preventive and punitive social spaces to prevent environmental damage they cause, weakening the legal systems of environment protection in order to continue the overexploitation according to their mercantilist and utilitarian approach. In this sense, all the damage caused to nature by companies is not part of their financial investments; it is part of their expenses as they do not internalize the cost it takes to produce goods. This makes goods more competitive and profitable because not they are paying the actual cost for the production of their goods and services. In face of these human activities, Faced with these destructive human activities, the capacity of regeneration of nature is largely insufficient.